Developing digital gamification for Abbasid history learning in seventh-grade Islamic religious education - Arifatul Ummiyah; Shokhibul Mighfar (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
Historical learning in Islamic Religious Education (IRE), particularly Abbasid history, remains dominated by teacher-centered instruction and memorization, limiting students’ engagement and conceptual understanding. Despite the proven benefits of digital gamification, evidence in IRE remains limited. This study aimed to develop and evaluate a digital gamification medium for Abbasid history and assess its effectiveness in enhancing seventh-grade students’ conceptual understanding. The study employed a Research and Development approach using the ADDIE model. The developed media was validated by media and subject-matter experts, while its instructional effectiveness was assessed through a one-group pretest–posttest design using the Wilcoxon Signed-Rank Test and normalized gain (N-Gain) analysis. Expert validation indicated that the developed medium achieved acceptable feasibility, with scores of 72.7% from media experts and 76.3% from subject-matter experts. Statistical analysis revealed a significant improvement between pretest and posttest scores (Asymp. Sig. = 0.000), while the average N-Gain score of 0.6693 indicated a high increase in students’ conceptual understanding. The findings suggest that instructional effectiveness resulted primarily from the constructive alignment between historical content, pedagogical design, and gamification mechanics rather than technological novelty alone. The study highlights the potential of pedagogically aligned digital gamification to enhance historical learning within IRE and provides practical guidance for integrating interactive learning environments into humanities- and religion-based education. This research extends the gamification literature into the underexplored domain of Abbasid history in IRE and demonstrates that meaningful cognitive improvement can be achieved through well-designed instructional integration without requiring sophisticated technological infrastructure.